Petrography and U-Pb SHRIMP zircon geochronology of basement samples from a key area in central Dronning Maud Land, East Antarctica: Implications for the eastern extension of the Grenville-age Maud Belt in Antarctica - Larsen, Stephen (The University of Bergen, 2017)
Central Dronning Maud Land, East Antarctica represents a key area for the understanding of previous supercontinent assemblies. This study reports U/Pb SHRIMP ages and petrographic descriptions for nine samples collected in central Dronning Maud Land during the GeoMaud 1995/96 expedition in East Antarctica. This study further densifies an interesting area with limited previous geochronological data. The new U/Pb ages reveal basement crystallisation ages ranging between ca. 1130–1025 Ma, indicating that the study area is a part of the Mesoproterozoic Maud Belt that formed along the margin of the Kalahari Craton. This is further supported by petrographic characteristics that reveal granodioritic to tonalitic protolithic compositions, indicating that the basement formed within a volcanic arc system. Subsequent metamorphism during the Late Mesoproterozoic was not recorded in this study. No igneous or metamorphic activity was present between ca. 1025–650 Ma. Mafic igneous formation prior to metamorphism was recorded at ca. 637 and 613 Ma. This could imply that the Mozambique ocean was not fully closed at that time. Subsequent Late Neoproterozoic/Early Paleozoic U/Pb ages recorded metamorphic ages at two different stages at ca. 590–550 Ma and ca. 530–510 Ma. These events are characterised by high-grade metamorphism. Petrographic characteristics point towards granulite facies metamorphism related to the “Pan-African” event during collision between parts of East and West Gondwana. Limited evidence points to earliest metamorphic age recorded at ca. 611 Ma, earlier than previously assumed. Recent aeromagnetic surveys revealed the sub-ice boundary between the Maud Belt and the Tonian Oceanic Arc Super Terrane (TOAST). This anomaly projects into central Dronning Maud Land. However, this study reveals that all samples belong to the Mesopreoterozoic Maud Belt, and that this boundary is not present within the study area. Thus, the boundary must be located slightly further east than previously proposed. Masteroppgave i ...